2011
DOI: 10.1007/s13311-011-0065-x
|View full text |Cite
|
Sign up to set email alerts
|

Myelin Regeneration in Multiple Sclerosis: Targeting Endogenous Stem Cells

Abstract: Regeneration of myelin sheaths (remyelination) after central nervous system demyelination is important to restore saltatory conduction and to prevent axonal loss. In multiple sclerosis, the insufficiency of remyelination leads to the irreversible degeneration of axons and correlated clinical decline. Therefore, a regenerative strategy to encourage remyelination may protect axons and improve symptoms in multiple sclerosis. We highlight recent studies on factors that influence endogenous remyelination and potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 88 publications
1
28
0
3
Order By: Relevance
“…In the present study, there was also an observed decrease in the amount of myelin after crushing (15 kgf), which is comparable with the density of nerve fibers diminished as reported by Oliveira et al [28]. Based on these facts, we suggest the use of this therapy as a possible treatment for diseases and injuries that lead to a loss of myelin, for example, multiple sclerosis, which is prevalent in young adults and affects 2.5 million people [29, 37]. The number of capillaries present in injured nerves was not altered by irradiation with LLLT after 10 and 21 days [35].…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, there was also an observed decrease in the amount of myelin after crushing (15 kgf), which is comparable with the density of nerve fibers diminished as reported by Oliveira et al [28]. Based on these facts, we suggest the use of this therapy as a possible treatment for diseases and injuries that lead to a loss of myelin, for example, multiple sclerosis, which is prevalent in young adults and affects 2.5 million people [29, 37]. The number of capillaries present in injured nerves was not altered by irradiation with LLLT after 10 and 21 days [35].…”
Section: Discussionsupporting
confidence: 85%
“…It is not completely understood why remyelination occurs so robustly in the periphery and so poorly in the CNS, though one hypothesis is that the environment after injury is hostile to OL terminal differentiation. In accordance with this hypothesis, a common feature of CNS lesions from patients with multiple sclerosis is an abundance of pre-myelinating OLs that fail to terminally differentiate (Huang et al, 2011). It is exciting to speculate on the use of both existing and to-be-developed zebrafish demyelination and remyelination models in genetic and small molecule screens, which could prove to be very important tools for elucidating molecular mechanisms that can promote or inhibit regeneration in the CNS of mammals (Buckley et al, 2008).…”
Section: Oligodendrocyte Development and Myelinationmentioning
confidence: 89%
“…112,113 For reasons discussed above, emphasis has been placed on the targeting of pathways that regulate differen tiation of OPCs into remyelinating oligo dendrocytes. This focus does not suggest that approaches to enhance OPC recruitment through migration and proliferation are obsolete but, rather, reflects the most recent research activity.…”
Section: Targets To Promote Remyelinationmentioning
confidence: 99%